1666. Sources and Preventability of Hospital-onset Bacteremia and Fungemia in the United States: Evaluation of a Potential Healthcare Quality Measure. (15th December 2022) - Leekha, Surbhi; Robinson, Gwen; Jacob, Jesse T; Fridkin, Scott; Shane, Andi L; Sick-Samuels, Anna; Milstone, Aaron; Nair, Rajeshwari; Perencevich, Eli N; Puig-Asensio, Mireia; Kobayashi, Takaaki; Mayer, Jeanmarie; et al.
Abstract: Background: Hospital-onset bacteremia and fungemia (HOB) is being proposed as a potential healthcare quality measure due to its clinical significance, objectivity, and ease of detection. However, information is lacking on sources of HOB and the proportion and types of cases considered preventable. Methods: We evaluated sources and potential preventability of HOB cases at 12 hospitals using retrospective chart review. HOB was defined as a positive blood culture >= day 4 (admission date=day 1) for one or more organisms. Stratified sampling of cases by commensal and noncommensal organisms was used. Infectious disease physicians determined the source of HOB and rated preventability from 1-6 (1=definitely preventable to 6=definitely not preventable) using a previously validated guide. Ratings of 1–3 were collectively considered potentially preventable and 4–6 likely not preventable. Results: We evaluated sources and potential preventability of HOB cases at 12 hospitals using retrospective chart review. HOB was defined as a positive blood culture >= day 4 (admission date=day 1) for one or more organisms. Stratified sampling of cases by commensal and noncommensal organisms was used. Infectious disease physicians determined the source of HOB and rated preventability from 1–6 (1=definitely preventable to 6=definitely not preventable) using a previously validated guide. Ratings of 1–3 were collectively considered potentially preventable and 4–6 likely not preventable. Figure 1 Distribution of microorganisms in noncommensal HOB cases. Figure 2 Sources of Noncommensal Hospital-onset Bacteremia and Fungemia Cases. Figure 3 Preventability Rating of Hospital-onset Bacteremia and Fungemia Cases. Conclusion: Gastrointestinal and endovascular sources account for a large majority of noncommensal HOB cases. A high proportion of noncommensal HOB cases are likely not preventable. The presence of non-preventable events should be considered when using HOB as a quality measure. Approaches to identifying the subset of preventable noncommensal HOB events should be explored. Disclosures: Scott Fridkin, MD, Pfizer: Grant/Research Support Andi L. Shane, MD, MPH, MSc, International Scientific Association for Probiotics and Prebiotics (ISAPP): travel and lodging to attend international meeting to deliver a presentation, June 2022 Aaron Milstone, MD, Merck: Grant/Research Support Rajeshwari Nair, MBBS, PhD, Vertex Pharmaceuticals: Salary.